Pengaruh Media Edukasi terhadap Pengetahuan Siswa Sekolah Dasar tentang Pencegahan Covid-19 - Novita Ayu Wardhany; Yeni Farida; Rasmaya Niruri (Jurnal Ilmiah Medicamento, 2022)
Covid-19 is a highly transmittable disease caused by viral infection. Children belong to the age group vulnerable to the transmission of COVID-19. Health promotion is important to provide a basic understanding of minimizing the incidence of transmission. The success of health promotion is influenced by the methods and media used. Comic and animation videos are considered capable of helping students in the learning process. This study was conducted to determine the level of knowledge of respondents who were given education through comics and animation media and to find out the difference in knowledge between the two media. Experimental pre-test and post-test designs were conducted. The educational media used are comics and animation videos. The research subjects were 5th-grade students of SDIT Insan Mulia Surakarta. Knowledge is assessed from the ability to answer questions correctly based on the educational material provided. The Wilcoxon test analysis was used to determine the differences in respondents' knowledge before and after giving the media and the Mann-Whitney test to determine the differences in respondents' knowledge between media. The results of the research on 42 respondents showed an increase in the pre-test and post-test scores in both groups. The mean pretest and post-test scores of the comic group were 7.86 and 9.17, while the mean score in the video animation group were 7, 89, and 8.68. Wilcoxon test result p-value of 0.001 in the comic media group and 0.004 in the animation media group. This study showed that there was no significant difference in knowledge of comics and animation group (p-value 0.200; P> 0.05). These results showed that both media have the same effectiveness in increasing respondents' knowledge of Covid-19 prevention.